Reconceptualization of Trochlear Dysplasia in Patients With Recurrent Patellar Dislocation Using 3-Dimensional Models. Issue 11 (21st November 2022) - Yu, Kristin E.; Cooperman, Daniel R.; Schneble, Christopher A.; McLaughlin, William; Beitler, Brian; Kaliney, Ryan; Wang, Annie; Fulkerson, John P.
Background: Common classification schemes, measurements, and surgical planning for trochlear dysplasia are predicated on 2-dimensional imaging views. Purpose: To investigate patellofemoral joint osseous anatomy using 3-dimensional (3D) printed models to describe osseous anatomic trochlear variations in patients with recurrent patellar dislocation. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Computed tomography scans were obtained from 20 patients with recurrent patellar dislocation and 10 healthy control knees, and 3D prints generated from these computed tomography scans were studied with respect to mediolateral positioning of the proximal trochlear groove and groove obliquity as well as changes in the appearance, height, and orientation of the medial and lateral trochlear ridges. Each trochlea was centered with respect to a vertical line perpendicular to the distal femoral condyles and through the central intercondylar notch roof, with the 3D models resting on their posterior femoral condyles. A novel 3D measurement method was devised to assess groove obliquity, termed the entry point–transition point (EP-TP) angle. The EP was defined as the midpoint of the flattened region of the proximal trochlea where the lateral and medial ridges of the proximal trochlea meet, and the TP was the point along the trochlear groove at which the groove shape changes from an oblique orientation proximally to one more vertical distally. Measurements were obtained by 3 reviewers, and reliability analyses were performed. Results: With the dysplastic knees arranged according to flattening of the trochleas, increased obliquity of the trochlear grooves was observed, as reflected by increased EP-TP angles as well as more lateral patellar EPs into the proximal trochleas of these recurrent patellar dislocation knees when compared with the control knees. The degree of trochlear dysplasia (according to the Dejour classification and trochlear flatness in the frontal and axial planes) was associated with diminished prominence of the lateral trochlear convexity, increasingly lateralized proximal trochlear EPs, increased trochlear groove obliquity, lateral trochlear curvature, and progressive medial ridge deformity. Conclusion: The 3D reproductions enabled unique conceptualization of trochlear deformity associated with recurrent patellar dislocation.